With submission to the requirements of the law, convicts, in penitentiaries actual problems of application of the legal system (Journal of actual problems of jurisprudence, 2019)
This article explores the methods and the development of the penal system in Kazakhstan.Keywords: the prison security, criminalized enforcement law, educational and correctional work, labor, convicted, custody.